Effect of Client Appraisal on the Financial Performance of Commercial Banks in Rwanda - Gloria, Mugeni Alaine; Kengere, Athanas Osiemo (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study assessed the effect of client appraisal on the financial performance of commercial banks in Rwanda. Using secondary data from audited quarterly financial statements of nine licensed commercial banks over the period 2018–2024, the research employed descriptive statistics and panel regression analysis. Client appraisal was measured through Non-Performing Loan (NPL) ratios and loan loss provisions, while financial performance was assessed using Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). The findings revealed that client appraisal significantly and positively influences financial performance (β = 0.42, p < 0.001), explaining substantial variance in profitability indicators. Banks with rigorous client appraisal mechanisms demonstrated lower Non-Performing Loan (NPL) ratios and higher profitability. The study concludes that effective client appraisal is critical for credit risk mitigation and financial stability in Rwanda's banking sector. It is recommended that banks strengthen credit assessment frameworks through advanced scoring models, comprehensive borrower evaluation, and regular staff training to sustain profitability and minimize default risks.